Selectivity of solid phase extraction of freshwater dissolved organic matter and its effect on ultrahigh resolution mass spectra. Issue 7 (1st July 2016) - Raeke, Julia; Lechtenfeld, Oliver J.; Wagner, Martin; Herzsprung, Peter; Reemtsma, Thorsten
Abstract : Solid phase extracts of freshwater dissolved organic matter are compared to the original sample with use of complementary techniques. Abstract : Solid phase extraction (SPE) is often used for enrichment and clean-up prior to analysis of dissolved organic matter (DOM) by electrospray ionization (ESI) coupled to ultrahigh resolution Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS). It is generally accepted that extraction by SPE is not quantitative with respect to carbon concentration. However, little information is available on the selectivity of different SPE sorbents and the resulting effect for the acquired DOM mass spectra. Freshwater samples were extracted by the widely used PPL, HLB and C18 sorbents and the molecular composition and size distribution of the DOM in the extracts and in the permeates was compared to the original sample. Dissolved organic carbon (DOC) recoveries ranged between 20% and 65% for the three tested SPE sorbents. Size-exclusion chromatography coupled to organic carbon detection (SEC-OCD) revealed that limited recovery by PPL and HLB was primarily due to incomplete elution of a fraction of apparent high molecular weight from the solid phase. In contrast, incomplete retention on the solid phase, mainly observed for the C18 cartridge, was attributed to a fraction of low molecular weight. The FT-ICR mass spectra of the original sample and the SPE extracts did not differ significantly in their molecular weight distribution, but they showed sorbent specific differences in the degree of oxygenation and saturation. We concluded that the selective enrichment of freshwater DOM by SPE is less critical for subsequent FT-ICR MS analysis, because those fractions that are not sufficiently recovered have comparatively small effects on the mass spectra. This was confirmed by the extraction of model compounds, showing that very polar and small molecules are poorly extracted, but also have a low response in ESI-MS. Of the three tested SPE cartridges the PPL material offered the best properties for DOM enrichment for subsequent FT-ICR MS analysis as it minimizes too strong and too weak DOM–sorbent interactions.